THE MEDIATING EFFECT OF JOB SATISFACTION ON THE LINK BETWEEN REWARD AND JOB PERFORMANCE: A CASE OF HOSPITALS IN PAKISTAN - Mirwise Khan; Faisal Khan; Aman khan; Muqadas Khan; Silvia Ahmed; Shah Hussain Awan; Bushra Bakhtiar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This study seeks to examine the relationship between reward and Job Performance. This study also investigates the role of Job satisfaction as a mediator between reward and Job performance. For this study, information was collected from hospitals in the twin cities of Pakistan. This deductive and descriptive study investigates the relationships between the variables. The population of the current research consists of hospital employees. The total data from 310 respondents were analyzed. According to the results of our study, both reward and job satisfaction significantly impact Job Performance, with Job satisfaction as a significant mediator between reward and job performance. This study’s findings and results have implications for future research and hospital-based organizations.